2015
DOI: 10.4103/1305-7456.149636
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of gingival health among school children in Sharjah, United Arab Emirates

Abstract: Objectives:The present study evaluated the gingival condition among school going children in Sharjah, United Arab Emirates and determined its relationship with tooth brushing frequency, diet and dental caries.Materials and Methods:Four hundred and five children participated in the study. There were 232 boys (57%) and 173 (43%) girls. Children were grouped based on age as ≤6 years (n = 84) mean age 4.72 ± 0.50 and >6 years (n = 321) mean age 8.47 ± 1.65. The amount of dental plaque and gingival condition were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 19 publications
5
27
2
Order By: Relevance
“…The statistical analysis of our own results did not reveal any correlation between gender and bleeding, although the research done by Gopinath et al showed that males were 2.11 times more likely to develop gingivitis than females. 22 However, in our study, a correlation was found between the amount of bacterial plaque and the likelihood of bleeding, which confirms a relationship of gingivitis etiology and the oral hygiene status. In children with poor oral hygiene, the likelihood of bleeding on probing was 4 times higher than in children with fair oral hygiene.…”
Section: Discussionsupporting
confidence: 81%
“…The statistical analysis of our own results did not reveal any correlation between gender and bleeding, although the research done by Gopinath et al showed that males were 2.11 times more likely to develop gingivitis than females. 22 However, in our study, a correlation was found between the amount of bacterial plaque and the likelihood of bleeding, which confirms a relationship of gingivitis etiology and the oral hygiene status. In children with poor oral hygiene, the likelihood of bleeding on probing was 4 times higher than in children with fair oral hygiene.…”
Section: Discussionsupporting
confidence: 81%
“…Age‐associated differences in OHS and gingival health are in congruence with prior observations 34 . Ramberg et al 33 clearly demonstrated reduced risk to gingivitis in children with primary dentition compared with children with mixed dentition.…”
Section: Discussionsupporting
confidence: 85%
“…GI scores for the study population were lower than those reported by Gopinath et al 34 for children in the United Arab Emirates, whereas scores for children aged 1 to 5 years are comparable with those reported for children in Yemen 35 . Unfortunately, differences in GI scores of children with a digit‐sucking habit cannot be discussed, since no such data in the public domain could be identified.…”
Section: Discussioncontrasting
confidence: 53%
“…Gingivitis that occurs in children is not a serious condition as adults, due to the differences in the quantity and quality of bacterial plaque (Karim et al 2013). Total accumulation of plaque in children varies according to the frequency of brushing their teeth (Gopinath et al 2015).…”
Section: The 2nd International Meeting Of Public Health 2016mentioning
confidence: 99%